PENGARUH KUALITAS LAYANAN DAN CITRA PERUSAHAAN TERHADAP KEPUASAN NASABAH PADA BANK OCBC NISP DI DENPASAR - Mulyaningsih, Luh Ayu; Suasana, I Gst Agung Ketut Gede (E-Jurnal Manajemen, 2016)
The purpose of this study was to determine the effect of service quality and corporate image at Bank OCBC NISP in Denpasar. This research was conducted at Bank OCBC NISP in Denpasar. The number of samples taken were 105 respondents, with a non-probability sampling method is purposive sampling. Data collected through questionnaires. Data analysis technique used is using regression analysis techniques. Based on the analysis found that the image of the company and significant positive effect on customer satisfaction at Bank OCBC NISP in Denpasar. Then the quality of service is also positive and significant impact on customer satisfaction at Bank OCBC NISP in Denpasar.
Keywords: kualitas layanan; citra perusahaan; kepuasan nasabah